2023
DOI: 10.3390/healthcare11131849
|View full text |Cite
|
Sign up to set email alerts
|

Research Hotspots in Psoriasis: A Bibliometric Study of the Top 100 Most Cited Articles

Oana Mirela Tiucă,
Silviu Horia Morariu,
Claudia Raluca Mariean
et al.

Abstract: (1) Introduction: Psoriasis is a chronic, immune-mediated disease that negatively impacts patients’ quality of life and predisposes them to cardiovascular or metabolic diseases. This paper aims to summarize the knowledge structure and future directions in psoriasis research by means of bibliometrics. (2) Material and methods: The Thomson Reuters Web of Science database was interrogated using preestablished keywords. A list of the top 100 most cited articles focusing solely on psoriasis was compiled and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 115 publications
(305 reference statements)
0
3
0
2
Order By: Relevance
“…Accordingly, we adopt the DDPP analytics model that circumvents the limitations in traditional bibliometric analysis on T100 articles, such as 7 graphs against too many graphs and tables, potentially overwhelming readers (e.g., 27 graphs and 15 tables in a single article) [ 31 ] ; clear graphs with the FLCA algorithm against those cluttered and unclear, with labels that are too small to read (not author-centered orientation) [ 31 ] ; using the FLCA for article classifications against those done manually [ 32 ] ; 712 and T100TJR articles against traditional T100 with a lack of comparison with articles outside of the top-cited list [ 33 ] ; ITV against T100 articles listed [ 34 ] ; and structured results using the DDPP model against the traditional unstructured framework for describing the characteristics of T100 articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we adopt the DDPP analytics model that circumvents the limitations in traditional bibliometric analysis on T100 articles, such as 7 graphs against too many graphs and tables, potentially overwhelming readers (e.g., 27 graphs and 15 tables in a single article) [ 31 ] ; clear graphs with the FLCA algorithm against those cluttered and unclear, with labels that are too small to read (not author-centered orientation) [ 31 ] ; using the FLCA for article classifications against those done manually [ 32 ] ; 712 and T100TJR articles against traditional T100 with a lack of comparison with articles outside of the top-cited list [ 33 ] ; ITV against T100 articles listed [ 34 ] ; and structured results using the DDPP model against the traditional unstructured framework for describing the characteristics of T100 articles.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] There is a lack of comparison with articles outside of the top-cited list (e.g., discussions are limited to the top 100 articles on psoriasis). [ 33 ] All top-cited articles are simply listed with Tables [ 34 ] for better comprehension (e.g., as seen in this article with a visual impact beam plot). [ 35 ] Results are often presented without a structured framework, such as the descriptive, diagnostic, predictive, and prescriptive analytics (DDPP) model, which could provide a more focused approach to analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found that bibliometric analyzes of psoriasis articles from different periods concluded that biologic treatments were the focus of research. This can be attributed to the dual critical roles that T cells play in psoriasis, serving as both contributors to the disease's pathogenesis and potential targets for therapeutic intervention [ [12] , [13] , [14] ]. Herein, a bibliometric analysis was conducted to assess research on T cells in psoriasis; we systematically analyzed research content, development trends, and noteworthy achievements regarding T cells in psoriasis over the past 20 years and identified potential directions for future research.…”
Section: Introductionmentioning
confidence: 99%
“…La integración del conocimiento es el tema de mayor envergadura por abordar, donde la diversidad del conocimiento es creciente. En uno de los buscadores más reconocidos se encontraron más de 56.000 artículos relacionados con psoriasis, en una búsqueda realizada hasta el 2023, lo cual es indicativo de esta inmensidad de información (2) . Incluso, desde la aparición de Internet y la tecnología, la tendencia es al aumento, donde se ha visto que desde el año 2007 hay hasta diez veces el número de publicaciones relacionadas con esta enfermedad (3) .…”
unclassified
“…La identificación de las temáticas de tendencia y relevancia que están en el momento que se quiere establecer, bajo el concepto de principio de oportunidad, implica las acciones de gestión efectiva. La aprobación de algún nuevo medicamento o de una nueva indicación para su administración obliga a la capacitación de los médicos que se van a ver enfrentados a la patología y a la comprensión del momento de utilización de estas tecnologías (1,2) . Aunque se parte de las bases del conocimiento, aparecen nuevos conceptos fisiopatológicos que exigen la actualización de los médicos que se graduaron varios años atrás.…”
unclassified